Wayang Golek as The Preservation of Javanese Culture Which is the Value of Local Culture,In Bintang Meriah Village BatangKuis District, Deli Serdang Regency - Harianto II Harianto II (PHILOLOGY Journal of English Language and Literature, 2021)
WayangGolek is part of Javanese culture, its existence has now changed in the third generation. This puppet show is precisely in BintangMeriah Village in BatangKuisDistrict,Deliserdang Regency the origin of Golek puppets was created from a community of musical arts. The musical facilities used are unique because all the musical equipment is made of bamboo, until one day the idea of one of the members of the music to initiate a cultural addition in a performance, this is intended so that fans of this music do not get bored with the music performance. Then cameWayangGolek whose creation is not far from the basic material that is bamboo. The taking of bamboo as the basic material in this art has a deep philosophy, where bamboo when blown by the wind he will remain strong at the root even of the bamboo tree. This illustrates that we must be able to keep up with the times by bringing the culture that we have.